Exploring the Role of Cognitive Emotion Regulation Strategies on the Quality of Life of HIV Patients: Role of Cognitive Emotion Regulation Strategies - Bhatti, Rabia Javed; Fahd, Samar; Rehman, Saif ur (Pakistan Journal of Health Sciences, 2023)
Quality of life (QoL) is recognized as an essential end point in the disease management of chronic conditions such as HIV. Cognitive impairments impact a broad spectrum of experiences and is a common issue affecting people living with HIV. Due to the chronicity of the illness, HIV/AIDS individuals’ experiences adverse psycho-social and emotional problems causing severe effect on the quality of life. Objective: To explore the impact of Cognitive Emotion Regulation Strategies on the Quality of Life of HIV patients. Besides, the study also explored the impact of adaptive and maladaptive Cognitive Emotion Regulation Strategies on the Quality of Life of HIV infected individuals. Methods: For the purpose of collecting data, a sample of (N = 50) HIV patients was acquired by means of convenient sampling for the present study from the specialized HIV clinics of South Punjab, Pakistan. The data were obtained through these standardized instruments’ Urdu versions; Cognitive Emotion Regulation Questionnaire (CERQ) and WHOQOL-HIV BREF. Results: The results showed a role of individuals’ Cognitive Emotion Regulation on the quality of life. The study further categorized the function with regard to both adaptive and maladaptive Cognitive Emotion Regulation Strategies on the HIV patient’s quality of life. Conclusions: The study endows the literature with empirical evidence by targeting a submerged and stigmatized population